THEORETICAL-PRACTICAL BASIS OF THE IDEAS OF BUKHARA JADIDS ON EDUCATION - Navfal Ashurov (European Science Publishing, 2024)
This article talks about the meaning of the word jadid, its origin, the founders of the jadid movement and their ideas. It also describes the struggle of the enlightened representatives of Bukhara for national independence and freedom.
Keywords: Jadids, Bukhara, people, humanity, purpose, education.